Dialysate Vascular Endothelial Growth Factor Is an Independent Determinant of Serum Albumin Levels and Predicts Future Withdrawal From Peritoneal Dialysis in Uremic Patients. Issue 5 (20th November 2013) - Hazama, Takuma; Fukami, Kei; Yamagishi, Sho‐ichi; Kusumoto, Takuo; Sakai, Kazuko; Adachi, Takeki; Sonoda, Kazuhiro; Kasuga, Syumon; Ueda, Seiji; Okuda, Seiya
Abstract Peritoneal protein loss due to high peritoneal permeability may contribute to hypoalbuminemia and early withdrawal from peritoneal dialysis (PD) therapy in end stage renal disease (ESRD) patients. We have found that pigment epithelium‐derived factor (PEDF) has anti‐vasopermeability properties both in cell culture and animal models by counteracting the biological actions of vascular endothelial growth factor (VEGF). However, it remains unknown which clinical variables, including dialysate VEGF and PEDF, are associated with decreased serum albumin levels and could predict early withdrawal from the PD in ESRD patients. We address these issues. Twenty‐seven ESRD patients undergoing PD were enrolled. Clinical variables were measured at 6 months after commencing PD. We examined the independent correlates of serum albumin in PD patients and then prospectively investigated the predictors of withdrawal from the PD therapy over 4 years. Dialysate VEGF was associated with peritoneal solute transport rate (P = 0.002), serum albumin (inversely, P < 0.001) and dialysate PEDF levels (P < 0.001). In multiple stepwise regression analysis, age (P = 0.002) and dialysate VEGF levels (P < 0.001) were independent determinants of serum albumin levels. High VEGF (>27 pg/mL), low serum albumin (≤3.31 g/dL) and low hemoglobin (≤11.2 g/dL) were correlated with withdrawal from the PD therapy during the 4 years. The odds ratio of dialysate VEGF for early withdrawal from the PD was 6.310 (P = 0.035). The present study demonstrated that increased dialysate VEGF was associated with decreased serum albumin and early withdrawal from the PD therapy. Inhibition of peritoneal VEGF production may be a therapeutic target in PD patients.